Co-management mangrove ecosystem in The Langge Village, Anggrek District, North Gorontalo Regency - Abudi, Miranti Khairunisa; Hamzah, Sri Nuryatin; Kasim, Faizal (Universitas Malikussaleh, 2022)
This research aimed to 1) determine the existing condition of Langge Village's mangroves and their utilization, 2) analyze stakeholders, the influence and mapping of co-management, and 3) analyze the form of co-management, roles, and responsibilities of stakeholders towards mangrove management in Langge Village. This research was conducted in August-November 2021. Mangrove vegetation data was collected using the line transect method; while the stakeholder data collection is done by open interviews. The data obtained from mangrove vegetation are frequency and density; while the stakeholders are in the form of interests, influence, implementation of co-management, and the roles and responsibilities of stakeholders. Based on this study, 16 species of true mangroves were found at 3 observation stations from Avicennia, Bruguiera, Ceriops, Rhizophora, Sonneratia, and Xylocarpus groups. Mangrove management in Langge Village is at the Advisory Committee stage or the advocacy stage.Keywords: Co-Management, stakeholders, management, mangrove